Safety of Statin Pretreatment in Intravenous Thrombolysis for Acute Ischemic Stroke. Issue 9 (September 2015) - Tsivgoulis, Georgios; Kadlecová, Pavla; Kobayashi, Adam; Czlonkowska, Anna; Brozman, Miroslav; Švigelj, Viktor; Csiba, Laszlo; Kõrv, Janika; Demarin, Vida; Vilionskis, Aleksandras; Jatuzis, Dalius; Katsanos, Aristeidis H.; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose— A recent meta-analysis investigating the association between statins and early outcomes in acute ischemic stroke (AIS) patients treated with intravenous thrombolysis (IVT) indicated that prestroke statin treatment was associated with increased risk of 90-day mortality and symptomatic intracranial hemorrhage. We investigated the potential association of statin pretreatment with early outcomes in a large, international registry of AIS patients treated with IVT. Methods— We analyzed prospectively collected data from the Safe Implementation of Treatments in Stroke-East registry (SITS-EAST) registry on consecutive AIS patients treated with IVT during an 8-year period. Early clinical recovery within 24 hours was defined as reduction in baseline National Institutes of Health Stroke Scale score of ≥10 points. Favorable functional outcome at 3 months was defined as modified Rankin Scale scores of 0 to 1. Symptomatic intracranial hemorrhage was diagnosed using National Institute of Neurological Disorders and Stroke, European-Australasian Acute Stroke Study-II and SITS definitions. Results— A total of 1660 AIS patients treated with IVT fulfilled our inclusion criteria. Patients with statin pretreatment (23%) had higher baseline stroke severity compared with cases who had not received any statin at symptom onset. After adjusting for potential confounders, statin pretreatment was not associated with a higher likelihood of symptomatic intracranial hemorrhage defined by any of the 3 definitions. Statin pretreatment was not related to 3-month all-cause mortality (odds ratio, 0.92; 95% confidence interval, 0.57–1.49; P=0.741) or 3-month favorable functional outcome (odds ratio, 0.81; 95% confidence interval, 0.52–1.27; P=0.364). Statin pretreatment was independently associated with a higher odds of early clinical recovery (odds ratio, 1.91; 95% confidence interval, 1.25–2.92; P=0.003). Conclusions— Statin pretreatment seems not to be associated with adverse outcomes in AIS patients treated with IVT. The effect of statin pretreatment on early functional outcomes in thrombolysed AIS patients deserves further investigation.